Hold still - LaCour, Nina.; Nolting, Mia. (New York, N.Y. : Dutton, 2009)
Ingrid didn't leave a note. Three months after her best friend's suicide, Caitlin finds what she left instead: a journal, hidden under Caitlin's bed.
Lexile: 770.
A Junior Library Guild selection
Keywords: Bereavement; Friendship -- Juvenile fiction; Psychological fiction; Bereavement -- Fiction; Suicide -- Fiction; Friendship -- Fiction; Young adult fiction